Can the multi-walled carbon nanotubes be used to alleviate the phytotoxicity of herbicides in soils?. (November 2021) - Yao, Ting; Liu, Lejun; Tan, Shuo; Li, Hui; Liu, Xiangying; Zeng, Aiping; Pan, Lang; Li, Xiaogang; Bai, Lianyang; Liu, Kailin; Xing, Baoshan
Abstract: Herbicides are commonly used globally. However, residual herbicides in soils for ages often result in phytotoxicity and serious yield loss to subsequent crops. In this paper, the multi-walled carbon nanotubes (MWCNTs) were utilized to amend the herbicide polluted soil, and the adsorption performance of herbicides to MWCNTs amended soil was studied. Results indicate efficient alleviation of herbicide-induced phytotoxicity to rice and tobacco due to MWCNTs amendment. When 0.4% MWCNTs were applied, the concentration of sulfentrazone that inhibited the same rice height by 50% (IC50 ) increased to more than 3 times that of pure soil. When the MWCNTs were used to alleviate the phytotoxicity of quinclorac to tobacco, the MWCNTs not only alleviated the phytotoxicity of quinclorac but also promoted the growth of tobacco. The MWCNTs amended soil significantly increased the adsorption of herbicide to soil than biochar. The soil microbial analysis shows that MWCNTs had no significant effect on soil microbial community diversity, but the long-term exposure to MWCNTs could change the structure of the soil microbial community. Above all, our results highlighted the potential implication of the MWCNTs to ensure crop production by promoting crop growth and reducing the residual bioavailability of herbicides. Highlight: The MWCNTs are better than biochar to alleviate the phytotoxicity of herbicides. MWCNTs simultaneously promote the growth of tobacco. The phytotoxicity alleviation was due to the reduced bioavailable concentration. The K d or K f of MWCNTs amended soil can be calculated from the logistic equation. MWCNTs long-term exposure did not change soil microbial diversity but the structure.